Une mission féministe ou une mission de femmes? Les Soeurs des Saints Noms de Jésus et de Marie au Pérou et au Brésil (1960-1985) - Laperle, Dominique (Études d'histoire religieuse, 2017)
Ce texte désire mesurer la place du féminisme dans l’expérience missionnaire des Soeurs des Saints Noms de Jésus et de Marie au Pérou et au Brésil entre 1960 et 1985. Pour plusieurs religieuses, l’idée de ministères traditionnels ou inédits dans de nouveaux champs apostoliques leur a permis d’élargir le sens de leur vocation. La question des femmes prendra, avec l’aggiornamento conciliaire, un nouvel élan. À travers un patient travail de fond, les SNJM se sont inculturées dans leurs différents milieux d’insertion en intégrant une vision d’avenir des femmes. Cette étude permet donc de revoir la nature même des fonctions missionnaires des religieuses et bouscule la vision genrée de l’apostolat. This text wishes to measure the role of feminism in the missionary experience of the Sisters of the Holy Names of Jesus and Mary in Peru and Brazil between 1960 and 1985. For several nuns, the idea of traditional or new apostolic works in the South American Field allowed them to expand the meaning of their vocation. The issue of women will take, with the Conciliar aggiornamento, a new impetus. Through a patient groundwork, SNJM are inculturated in their different backgrounds of insertion by integrating a vision of the future of women. This study makes it possible to review the nature of the missionary religious functions and hustles the vision of gender of the apostolate and empowerment of religious women.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique latine; amériques; brésil; discipline; fem1000; femmes*; histoire; premier cycle; périodes historiques; pérou; ressource en ligne; régions géographiques; science des religions; sciences humaines

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales